Ethnobotanical and Phytopharmacological attributes of Mesua ferrea: A mini review - Muhammad Asif, Seyedeh Fatemeh Jafari, Zafar Iqbal, Vageesh Revadigar, Chern Ein Oon, Aman Shah Abdul Majid, Amin Malik Shah Abdul Majid (Journal of Applied Pharmaceutical Science, 2017)
Members of guttiferae family are widely distributed in the tropical areas of the world, especially Asian countries and are traditionally used by the local people for the treatment of various ailments ranging from headache to cancer. Mesua ferrea L. is an important member of this family, which has been shown to possess multifactorial pharmacological activities. This review highlights the traditional uses, phytochemical profiling and proven pharmacological attributes of different parts of M. ferrea. Almost every part of the plant is reported to have beneficial medicinal properties that can help to fight against different aliments. However, further studies are still required to explore the molecular targets responsible for the observed pharmacological activities and to test the efficacy of isolated compounds or standardized extracts in properly designed experiments. In addition, long term toxicity studies are also required to establish the safety profile of isolated compounds/standardised extracts before the commencement of clinical trials.
Keywords: Mesua ferrea, guttiferae, anticancer, antioxidant, anti-inflammatory, standardised extract.